Factors Associated With the Improvement of Left Ventricular Systolic Function by Continuous Positive Airway Pressure Therapy in Patients With Heart Failure With Reduced Ejection Fraction and Obstructive Sleep Apnea - Naito, Ryo; Kasai, Takatoshi; Dohi, Tomotaka; Takaya, Hisashi; Narui, Koji; Momomura, Shin-ichi (Frontiers in Neurology, 2022)
Background: Obstructive sleep apnea (OSA) is a potential risk factor for cardiovascular diseases, including arrhythmia, coronary artery disease, and heart failure (HF). Continuous positive airway pressure (CPAP) therapy is an effective therapy for OSA and the underlying HF partly through a 5–9% increase in the left ventricular ejection fraction (LVEF). However, data on the factors associated with the efficacy of CPAP on LVEF in patients with HF complicated by OSA is scarce. This study aimed to investigate whether LVEF improves in patients with OSA and HF after one month of CPAP therapy and to clarify which factors are associated with the degree of LVEF improvement. Method: This was a prospective, single-arm, open-label study. We enrolled moderate-to-severe OSA patients with HF who were being followed up at the cardiovascular center of Toranomon Hospital (Tokyo, Japan). Parameters of sleep study and LVEF were assessed at baseline and after one month of CPAP. Multivariate regression analyses with changes in LVEF as a dependent variable were performed to determine the factors that were associated with the degree of LVEF improvement. Results: We analyzed 55 consecutive patients with OSA and HF (mean age: 60.7 ± 12.2 years , mean LVEF value: 37.2 ± 9.8%). One month of CPAP treatment decreased the apnea-hypopnea index (AHI) from 45.3 ± 16.1 to 5.4 ± 4.1 per hour, and LVEF improved from 37.2 ± 9.8 to 43.2 ± 11.7%. Multivariate regression analyses demonstrated that age and body mass index were significant determinants of LVEF improvement. Conclusion: LVEF improved significantly after one month of CPAP therapy in Japanese patients with OSA and HF. Multivariate regression analyses indicated that an improvement in LVEF was likely to be observed in young obese patients.